Development of a Silicone-Based Polymer Matrix as a Suitable Transdermal Therapeutic System for Diallyl Disulfide - Szabolcs László; Zsófia Hajna; Attila Egyed; Erika Pintér; Ödön Wagner (MDPI AG, 2022)
There is an unmet need for novel therapeutic tools relieving chronic pain. Hydrogen sulfide (H2S) is highly involved in pain processes; however, the development of ideal matrices for sulfide donor compounds remains a great pharmaceutical challenge. We aimed to establish a suitable transdermal therapeutic system (TTS) using the H2S donor diallyl disulfide (DADS) as a model compound. After the preparation of DADS, its solubility was investigated in different liquid excipients (propylene glycol, polyethylene glycol, silicone oil) and its membrane diffusivity was assessed in silicone matrices of different compositions. Drug-releasing properties of DADS-containing patches with different silicone oil contents were determined with Franz and flow-through cells. We found a correlation between the liquid excipient content of the patch and the diffusion rate of DADS. DADS showed the best solubility in dimethyl silicone oil, and the diffusion constant was proportional to the amount of oil above the 3 m/m% threshold value. The 8-day-old patch showed a significantly lower, but better-regulated, drug release over time than the 4-day-old one. In conclusion, the silicone-based polymer matrix developed in this study is suitable for stable storage and optimal release of DADS, providing a good basis for a TTS applied in chronic pain.